2023
DOI: 10.3390/ani13142278
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rainbow Trout (Oncorhynchus mykiss) Intestinal In Vitro Platform for Profiling Amino Acid Digestion and Absorption of a Complete Diet

Abstract: The ever-increasing number and variation of raw materials utilized to provide alternative feed formulations continues to allow for a more sustainable and flexible approach. Testing all these options in vivo is still the most robust and reliable manner to pick the best raw material candidates, but it requires the use of large numbers of animals and is time-consuming and expensive. Therefore, we are developing an in vitro platform that can provide a reliable evaluation of new ingredients. The main aim of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
(52 reference statements)
1
0
0
Order By: Relevance
“…Therefore, brush border enzymes are considered reliable markers of intestinal cellular activity and functionality. Although TEM investigation did not show the presence of microvilli on the apical surface of the epithelial cells, gene expression analysis revealed that RTpiMI cells in all culture conditions actively transcribed leucine (LAP) and alanine (ALP) aminopeptidase genes, as we previously described [44]. The histochemical detection of LAP and ALP activity further demonstrated their translation into active enzymes.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, brush border enzymes are considered reliable markers of intestinal cellular activity and functionality. Although TEM investigation did not show the presence of microvilli on the apical surface of the epithelial cells, gene expression analysis revealed that RTpiMI cells in all culture conditions actively transcribed leucine (LAP) and alanine (ALP) aminopeptidase genes, as we previously described [44]. The histochemical detection of LAP and ALP activity further demonstrated their translation into active enzymes.…”
Section: Discussionsupporting
confidence: 47%